MRI assessment of excess cardiac iron in thalassemia major: When to initiate?. Issue 3 (7th July 2015) - Chen, Xiaodong; Zhang, Zuoquan; Zhong, Jinglian; Yang, Qihua; Yu, Taihui; Cheng, Ziliang; Chan, Queenie; Guo, Hua; Liang, Biling
<x xml:space="preserve">Abstract</x> Background To determine optimal initial age of cardiac iron screening with magnetic resonance imaging (MRI) T2* in patients with thalassemia major (TM). Methods We retrospectively reviewed black blood cardiac T2* assessments from 102 TM patients from the ages of 3 to 32 years. Cases of patients under and above 7 years old with detectable cardiac iron overload were analyzed separately. Associations between cardiac T2* and various factors, such as serum ferritin (SF), patient age and hepatic T2*, were assessed using either scatterplots or regression. Images were evaluated by two independent radiologists. Results With a T2* cut‐off value of 20 ms, no patient under 5 years old showed cardiac iron overload. Three of 19 (15.8%) patients under 7 years of age had a cardiac T2* ≤ 20 ms (5.5 to 7 years) but none had ≤10 ms, while 35 of 83 (42.2%) patients above 7 years old had a cardiac T2* ≤ 20 ms (8 to 32 years) and 18 of them ≤10 ms. Cardiac T2* correlated weakly with serum ferritin and liver T2* (r = −0.39 and 0.41, respectively, both P < 0.001), but not with patient age (P > 0.05). Conclusion Cardiac iron overload can occur in young TM patients, even as young as 5.5 years old. Assessment of cardiac iron with T2* might need to begin as early as 5 years old if suboptimal chelation therapy is administered. J. Magn. Reson. Imaging 2015;42:737–745.